Severe lactic acidosis due to excessive consumption of Cellucor C4 exercise supplement. Issue 5 (22nd October 2021) - Rajchgot, Jason; Hamilton, Mika; Wong, David K.; Fischer, Sandra; Leligdowicz, Aleksandra
Abstract: Lactic acidosis is a common laboratory abnormality encountered in hospitalized patients with a broad differential diagnosis encompassing many life-threatening etiologies. Here, we present a case of a patient with a persistently elevated lactate attributed to the use of a pre-workout supplement called Cellucor C4 . The use of herbal and dietary supplements is increasingly common, with low disclosure rates to health care practitioners. This case highlights the importance of considering rare causes of lactic acidosis in the absence of hemodynamic instability. It emphasizes the importance of obtaining a detailed history of non-prescription drugs, including herbal and dietary supplements, and illustrates the potential risks associated with the use of these unregulated products.